Occurrence and Fate of Nonylphenol Ethoxylates and Their Derivatives in Nansi Lake Environments, China. (1st January 2013) - He, Fang; Niu, Lingling; Aya, Obara; Wang, Shilong; Wang, Liguo
Abstract : The vertical and horizontal distribution of nonylphenol polyethoxylates (NPEOn, n = number of ethoxy units) and their derivatives in the Upper Nansi Lake, North China, were investigated using high‐performance liquid chromatography (HPLC) and liquid chromatography‐tandem mass spectrometry (LC‐MS/MS) methods. For the water‐phase concentrations of these compounds, data are omitted because of their low concentration levels. The content of NPEOn ( n = 1 to 15) bound onto the sediment of this lake changed in the range of 60.7 to 631.5 μg/kg dry for sediment cores with a thickness up to 350 mm. A typical increasing trend of the nonylphenol (NP) content was revealed along the water flow direction of this lake. Carbonated NPEOn (NPEn C) showed an increasing trend from upstream to downstream, with the total concentrations of the NPEOn falling in the range of 2.13 to 23.1 μg/kg dry. Results indicate that this lake received some effluent from wastewater treatment plants, whose treatment ratios are relatively low in this area. The nonoxidative hydrolytic transformation is a significant process occurring within the sediment phase of Nansi Lake.